2018
DOI: 10.1016/j.brs.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal deep brain stimulation modulates excessive cortical high β phase amplitude coupling in Parkinson disease

Abstract: Similar to STN-DBS, GPi-DBS reduces motor cortical β-γ PAC, like that also reported with dopaminergic mediations, suggesting it is a generalizable symptom biomarker in PD, independent of therapeutic target or proximity to the hyperdirect pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 63 publications
7
58
0
Order By: Relevance
“…Together with beta-band power, and corticocortical and basal ganglia/ cortical coherence, cortical PAC was associated with bradykinesia and rigidity 78 and lowered by therapeutically beneficial DBS in the STN or GPi. [79][80][81] As is true for other oscillatory activities (see above), increased cortical PAC is not specific for PD, but also occurs in patients with (isolated) dystonia 82 or essential tremor. 83 Studies of subcortical PAC in parkinsonian patients have focused on LFP recordings from the STN and GPi.…”
Section: Altered Firing Patterns and Oscillationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Together with beta-band power, and corticocortical and basal ganglia/ cortical coherence, cortical PAC was associated with bradykinesia and rigidity 78 and lowered by therapeutically beneficial DBS in the STN or GPi. [79][80][81] As is true for other oscillatory activities (see above), increased cortical PAC is not specific for PD, but also occurs in patients with (isolated) dystonia 82 or essential tremor. 83 Studies of subcortical PAC in parkinsonian patients have focused on LFP recordings from the STN and GPi.…”
Section: Altered Firing Patterns and Oscillationsmentioning
confidence: 84%
“…In studies of ECoG and EEG signals from PD patients, the amplitude of gamma‐band oscillations was found to be abnormally coupled to the phase of ongoing beta‐band oscillations in a process called phase‐amplitude coupling (PAC). Together with beta‐band power, and corticocortical and basal ganglia/cortical coherence, cortical PAC was associated with bradykinesia and rigidity and lowered by therapeutically beneficial DBS in the STN or GPi . As is true for other oscillatory activities (see above), increased cortical PAC is not specific for PD, but also occurs in patients with (isolated) dystonia or essential tremor …”
Section: Parkinsonism As Dysfunction Of the Basal Ganglia Thalamocortmentioning
confidence: 92%
“…Once again thalamic DBS and GPi DBS showed a similar pattern, but DBS to the GPe did not. Recent work has shown that GPi DBS has a similar effect on beta oscillations as STN DBS (Malekmohammadi et al, 2018). There are no accounts of the effect of human GPe DBS on beta-band activity in the brain, and while the presence of such oscillations can also be an aspect of healthy physiological brain activity, this demonstrates the ability of DBS via STN, GPi or thalamus to suppress beta frequency oscillations, and hypothesizes that GPe DBS may act via a different mechanism as previously suggested (Vitek et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that PAC is elevated in untreated PD patients compared to treated Swann et al, 2015;Malekmohammadi et al, 2018). It also emerges during the induction of severe parkinsonian symptoms in non-human primate models, and is related to disease severity (Devergnas et al, 2017).…”
Section: Mechanisms Of Waveform Shape Asymmetry and Pacmentioning
confidence: 99%
“…While conventional signal processing measures, such as beta power, have failed to reliably differentiate PD as a function of severity or diagnosis at the cortex (Stoffers et al, 2007;de Hemptinne et al, 2013;George et al, 2013;de Hemptinne et al, 2015;Swann et al, 2015;Malekmohammadi et al, 2018), novel metrics such as phase-amplitude correlations between beta and broadband gamma (50-150 Hz) (phase-amplitude coupling, PAC) have proven more promising. Specifically, PAC over motor cortex detected using electrocorticography (ECoG) is elevated in PD compared to other groups (de Hemptinne et al, 2013) and is reduced with DBS in a clinically-relevant manner Malekmohammadi et al, 2018). Interestingly, following characterization of PAC with ECoG, it was demonstrated that elevated PAC can also be detected non-invasively with scalp electroencephalography (EEG) .…”
Section: Introductionmentioning
confidence: 99%